La educación sexual en el proceso educativo de las estudiantes de décimo grado del subnivel superior básico del colegio experimental Pío Jaramillo Alvarado sección matutina del barrio Máximo Agustín Rodríguez de la parroquia San Sebastián del cantón y provincia de Loja, año lectivo 2012 – 2013 - Espinoza Díaz, Lucy Maribel (2014)
This research is related to sex education in the Educational Process aims to improve the sexual orientation in students. It constitutes an important contribution in the Educational Process of college students Pío Jaramillo Alvarado in the process of teaching and learning, this research work to achieve an overall objective in establishing research analyze the quality of sex education was proposed during Educational process in college students in the prospect of purposefully contribute to the improvement of teaching and learning processes of students. This sex education in the Educational Process and diagnosis of the current state in which students are theoretically substantiated, and thus propose feasible solution paths, to comply with the objectives formulated in the process of developing research was used as the main focus of the scientific method., inductive method that is based on theoretical knowledge, analytical method and the statistical method that allowed analyzing and presenting final results to overcome these difficulties to the problem. The population taken as reference for implementation was thus decided to requirements preset in scientific research whose precise informants were 73 students and 6 teachers, which enabled purchase real information through the application of research tools such as surveys, surveys for truthful and objective information, and from there to issue precise criteria to the existing problems in the institution. The results of studies that analyzed the 50.68% of students report that their teachers guide them much about Sex Education in the Educational Process during daily classes while a 49.32% of the students mentioned that their orientation sex is very low so you are worrying problems